Compressive bandaging in the therapy of ulcus cruris - Simović, Sonja (Medicinski časopis, 2021)
Compressive bandaging in the therapy of ulcus crurisSonja Simović, Health Center KragujevacABSTRACTUlcus cruris is ulceration located on the skin of the lower extremities. In most cases, it is a result of chronic vein blood flow insufficiency. Risk factors for developing ulceration are: varicosity, throbosis of deep veins, obissity and reduced physical activity. The main goal of this paper is to point out the benefits of compressive bandaging in epithelialization of ulcus. Case study: Patient A. J., 68 years old, professional construction worker, goes to the GP of his choosing due to pain in the area of his left leg wrist. After the examination, GP concludes that the patient has been suffering the ulceration for approximately past 3 months. Additional anamnesis: increased blood pressure, high cholesterol and triglycerides values, the patient has been smoking for the past 30 years. After consultative exemitations did by a vascular surgent, compressive bandaging has been conducted on the patient for 12 weeks. On controle exemination after the therapy, it has been found that the ulcus is completely epithelialized. Furthermore, GP suggested wearing compressive socks for two more years to prevent the formation of new ulceration. Appropriate compressive therapy in patients with ulcus cruris has multiple benefits: significant reduction of healing time, fast pain relief, reduction of healing costs and less necessary visits to the doctor. Keywords: ulcus cruris, compressive bandaging, vein blood flow insufficiency
Keywords: Keywords: ulcus cruris, compressive bandaging, vein blood flow insufficiency